Preventive home visits postpone mortality - a controlled trial with time-limited results - Stenlund Hans; Hellner Britt Mari; Dahlgren Lars; Sahlen Klas-Göran; Lindholm Lars (BMC, 2006)
Abstract Background There is a debate on whether preventive home visits to older people have any impact. This study was undertaken to investigate whether preventive home visits by professional health workers to older persons can postpone mortality in a Swedish context. Method A controlled trial in a small community in the north of Sweden. Participants are healthy pensioners aged 75 years and over. 196 pensioners were selected as the intervention group and 346 as the control group. The intervention, two visits per year, lasted two years. Results During the intervention, mortality was 27 per 1000 in the intervention group and 48 per 1000 in the control group. The incidence rate ratio for the control group IR2000-2001 was 1,79 (95%CI = 0,94-3,40). Analysing the data with an "on treatment approach" gave a significant result, 2,31 (95%CI = 1,07-5,02) After the trial the difference between the groups disappeared. Conclusion Preventive home visits in a healthy older population can postpone mortality in a Swedish context if they are carried out by professional health-workers in a structured way. When the home visit programme ended the effect on mortality disappeared. These findings are dependent on contextual factors that make it difficult to form general policy recommendations.